2022
DOI: 10.1007/s10566-022-09677-x
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Psychological Maladjustment/Adjustment: A Meta-Analytic Approach with Children and Adolescents Exposed to Natural Disasters

Abstract: Background Following disasters, children and adolescents can use coping strategies to feel better. A growing body of studies investigated the relation between them and maladjustment/adjustment, i.e., negative symptomatology/positive indicators of development. Yet, these constructs are studied separately. Objective We conducted two meta-analyses to examine the mean correlation between disaster-related coping strategies and indicators of maladjustment/adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 122 publications
1
15
0
1
Order By: Relevance
“…Not surprisingly, there were few mentions of maladaptive strategies—helplessness and escape (need for competence), and opposition (need for autonomy) being the ones mentioned. Our results were in line with published reports exploring the use of adaptive or maladaptive coping strategies in the context of natural disasters such as earthquakes or pandemics ( Raccanello et al, 2021a , b , 2022a ). For the second pamphlet, we relied both on the first pamphlet and on relevant guidelines for PFA ( NCTSN and NCPTSD, 2006 ; World Health Organization et al, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Not surprisingly, there were few mentions of maladaptive strategies—helplessness and escape (need for competence), and opposition (need for autonomy) being the ones mentioned. Our results were in line with published reports exploring the use of adaptive or maladaptive coping strategies in the context of natural disasters such as earthquakes or pandemics ( Raccanello et al, 2021a , b , 2022a ). For the second pamphlet, we relied both on the first pamphlet and on relevant guidelines for PFA ( NCTSN and NCPTSD, 2006 ; World Health Organization et al, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis indicated that, for child and adolescent victims of natural disasters, problem solving, support seeking, and submission have an adaptive role, while escape, social isolation, submission, and opposition are maladaptive ( Raccanello et al, 2022a ). A similar pattern was shown for COVID-19 pandemics where escape and social isolation were linked to traumatic symptoms, while problem solving, self-reliance, social support, and accommodation were related to adaptation ( Raccanello et al, 2021b ).…”
Section: Background and Rationalementioning
confidence: 99%
“…Based on our findings, we could argue that the pandemic urges not only the adoption of measures aimed at protecting physical health, but also psychological interventions to help children and adolescents coping with it. Young people have a large variety of resources that enable them, for example, to benefit from information and activities fostering their knowledge about the characteristics of a disaster, the protective behaviors, the associated emotions, and the emotional strategies deputed to manage them (Raccanello et al, 2020a(Raccanello et al, , 2020c. However, our results can be viewed focusing on the bright side of the medal: about 80% of the participants did not show the disorders and/or symptoms at issue.…”
Section: Discussionmentioning
confidence: 79%
“…hemot. eu; Raccanello et al, 2020aRaccanello et al, , 2020bRaccanello et al, , 2020cRaccanello et al, , 2021Raccanello et al, , 2022bVicentini et al, 2020).…”
Section: Current Study and Research Questionsunclassified
“…These strategies are typically activated in the face of perceived challenges or threats (for a more detailed description, see Zimmer‐Gembeck & Skinner, 2011; for applications, see Burro et al, 2021; Raccanello, Vicentini, Rocca, et al, 2020, Raccanello et al, 2021; Vicentini, Burro, et al, 2022). A meta‐analysis of data on natural disasters indicated that for children and adolescents, strategies such as problem solving and support seeking are positively associated with indicators of wellbeing, while strategies such as escape, delegation, social isolation, and opposition are positively associated with traumatic symptoms (Raccanello et al, 2023). A study using a sample of adults as reporters, indicated that the most effective strategies that children can use to cope with earthquakes are problem solving, information seeking, self‐reliance, support seeking, and accommodation (Raccanello et al, 2021).…”
Section: Introductionmentioning
confidence: 99%